2012
DOI: 10.1148/radiol.11111789
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Digital Breast Tomosynthesis System: Dosimetric Characterization

Abstract: Ioannis Sechopoulos, PhD Purpose:To comprehensively characterize the dosimetric properties of a clinical digital breast tomosynthesis (DBT) system for the acquisition of mammographic and tomosynthesis images. Materials and Methods:Compressible water-oil mixture phantoms were created and imaged by using the automatic exposure control (AEC) of the Selenia Dimensions system (Hologic, Bedford, Mass) in both DBT and full-field digital mammography (FFDM) mode. Empirical measurements of the x-ray tube output were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
96
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(99 citation statements)
references
References 26 publications
1
96
0
2
Order By: Relevance
“…The current MGD used for DBT is around 1.5 mGy for an average breast with 50% glandularity (Sechopoulos et al 2007, Feng and Sechopoulos 2012, Sechopoulos et al 2014. In this study, the impact of dose on the 3D imaging performance is evaluated by varying the calculated MGD values from 0.5 to 1.5 mGy ( Figure 9).…”
Section: Impact Of Mean Glandular Dosementioning
confidence: 99%
“…The current MGD used for DBT is around 1.5 mGy for an average breast with 50% glandularity (Sechopoulos et al 2007, Feng and Sechopoulos 2012, Sechopoulos et al 2014. In this study, the impact of dose on the 3D imaging performance is evaluated by varying the calculated MGD values from 0.5 to 1.5 mGy ( Figure 9).…”
Section: Impact Of Mean Glandular Dosementioning
confidence: 99%
“…Where errors in CBT occur in a clinical setting, the technical factors to form the mammogram (tube voltage [kVp], target material and filter material) might change due to the use of automatic exposure control (AEC) 33 , and this in turn would affect the VBD 34 . Feng et al 33 found the tube voltage to change with approximately 1kVp per cm in CBT and a shift from Rhodium to Silver filter from 6 cm to 7 cm CBT.…”
mentioning
confidence: 99%
“…Feng et al 33 found the tube voltage to change with approximately 1kVp per cm in CBT and a shift from Rhodium to Silver filter from 6 cm to 7 cm CBT. 33 If the CBT is lower than actual thickness,…”
mentioning
confidence: 99%
“…And finally, dosimetric characterization of breast imaging systems that are also based on Monte Carlo simulations could leverage our PCA model's ability to randomly generate breasts of different clinically relevant shapes quickly. 19,42,43 It is also important to note that the PCA models developed here, and the methodology we have employed, can be used independently of our automated edge detection algorithm. Any user-defined breast edge representation can be used in conjunction with our model to expand the basis of the model or to characterize a breast shape by condensing information down to a few principal components.…”
Section: Discussionmentioning
confidence: 99%